A novel mutation of gene in a patient with diazoxide-unresponsive congenital hyperinsulinism - Ji Sook Park; Hong-Jun Lee; Chan-Hoo Park (Korean Journal of Pediatrics, 2016)
Congenital hyperinsulinism (CHI) is a rare condition that can cause irreversible brain damage during the neonatal period owing to the associated hypoglycemia. Hypoglycemia in CHI occurs secondary to the dysregulation of insulin secretion. CHI has been established as a genetic disorder of islet-cell hyperplasia, associated with a mutation of the ABCC8 or KCNJ11 genes, which encode the sulfonylurea receptor 1 and the inward rectifying potassium channel (Kir6.2) subunit of the ATP-sensitive potassium channel, respectively. We report the case of a female newborn infant who presented with repetitive seizures and episodes of apnea after birth, because of hypoglycemia. Investigations revealed hypoglycemia with hyperinsulinemia, but no ketone bodies, and a low level of free fatty acids. High dose glucose infusion, enteral feeding, and medications could not maintain the patient's serum glucose level. Genetic testing revealed a new variation of ABCC8 mutation. Therefore, we report this case of CHI caused by a novel mutation of ABCC8 in a half-Korean newborn infant with diazoxide-unresponsive hyperinsulinemic hypoglycemia.